Stable transmission and expression of the hepatitis B virus total genome in hybrid transgenic mice until F10 generation - (:unkn) unknown (WILEY, 2006)
The aim of the present study was the generation of transgenic mice carrying the complete Hepatitis B Virus (HBV) genome and investigation of the presence of Hepatitis B surface antigen (HBsAg) expression through successive generations. Transgenic mice were generated by microinjecting HBV genome into fertilized eggs. Integration and expression of HBsAg in transgenic mice were analyzed by genomic DNA PCR, Southern and slot blots and enzyme-linked immunosorbent assay (ELISA). Expression was also confirmed by Western blotting and RT-PCR. Histological changes in liver tissue of transgenic mice were examined by HE staining. The HBV genome was transmitted to the F10 generation and the presence of HBV X gene transcripts was confirmed by RT-PCR analysis using liver cDNAs from the F10 generation mice. During an observation period of 2.5 years, mice were sacrificied and their organs subjected to histopathological examination. In the liver, slight histopathologic alterations were observed but none of these lineages had any hepatocellular carcinoma (HCC). HBV DNA can be stably transmitted and expressed in the transgenic mice until F10 generation. However, although we showed the presence of X gene transcripts in liver tissues of F10 generation mice by RT-PCR in these animals, long-term expression of the HBV complete genome and expression of X protein in hepatocytes did not cause neoplasia during the life span and HCC. These transgenic mice should be useful for detailed studies of the replication and expression of HBV and for physiological studies of HBV genome.
Keywords: SURFACE-ANTIGEN HBSAG; X-PROTEIN; HBX GENE; MOUSE; REPLICATION; DNA; PARTICLES; EMBRYOS; LIVER